2019
DOI: 10.3390/jcm8101577
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Mutations and Dysregulation of the MAP Kinase Pathway Associated to Sinonasal Mucosal Melanomas

Abstract: Sinonasal mucosal melanoma (SNM) is a rare and aggressive type of melanoma, and because of this, we currently have a limited understanding of its genetic and molecular constitution. The incidence among SNMs of somatic mutations in the genes involved in the main molecular pathways, which have been largely associated with cutaneous melanoma, is not yet fully understood. Through a next-generation sequencing (NGS) approach using a panel of 25 genes involved in melanoma pathogenesis customized by our group, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
1
8
1
Order By: Relevance
“…BRAF mutations were more common in the nasopharynx/other locations than in the nasal cavity and paranasal sinuses, while NRAS mutations were more common in the nasal cavity/paranasal sinuses. A clinical analysis of 25 patients with melanoma in the nasal cavity and paranasal sinuses showed that BRAF (32%) was the most common mutation type, followed by RAS (12%) and C-KIT (12%) [21]. There were fewer patients in that study compared with ours, and this has probably resulted in the difference in conclusions.…”
Section: Discussioncontrasting
confidence: 61%
“…BRAF mutations were more common in the nasopharynx/other locations than in the nasal cavity and paranasal sinuses, while NRAS mutations were more common in the nasal cavity/paranasal sinuses. A clinical analysis of 25 patients with melanoma in the nasal cavity and paranasal sinuses showed that BRAF (32%) was the most common mutation type, followed by RAS (12%) and C-KIT (12%) [21]. There were fewer patients in that study compared with ours, and this has probably resulted in the difference in conclusions.…”
Section: Discussioncontrasting
confidence: 61%
“…Malignant Melanoma represents a malignancy showing evidence of melanocytic differentiation that can be identified histopathologically or ultrastructurally [13], it is characterized by a high tendency to metastasize and striking resistance to conventional therapies other than surgery [14]. According to American Cancer Society about 100,350 new cases of melanoma will be diagnosed in 2020, and 6,850 people are expected to die of melanoma (www.cancer.org).…”
Section: Primary Oral Mucosal Melanomamentioning
confidence: 99%
“…Melanoma are malignant neoplasm that develop from melanocytes localized in the skin or mucosa, some of them come from pre-existing nevi, and they represent a significant and increasing public health concern and research subject [14][15][16]. Although melanoma represents 1% of all diagnosed skin cancer, it is the main cause of most skin cancer-related deaths, with a 5 year survival rate 20%.…”
Section: Melanomamentioning
confidence: 99%
“…Although melanoma represents 1% of all diagnosed skin cancer, it is the main cause of most skin cancer-related deaths, with a 5 year survival rate 20%. Cutaneous melanomas are the most common type, followed by mucosal melanomas and lastly the ocular melanoma, although primary mucosal melanomas are rare, they have a worse prognosis compared to the cutaneous counterpart [14,15,[17][18][19].…”
Section: Melanomamentioning
confidence: 99%